2017
DOI: 10.1111/bdi.12519
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in patients with major depression is related to bipolarity and mixed features: evidence from the BRIDGEIIMix study

Abstract: Objectives: BRIDGE-II-MIX study aimed to estimate the frequency of mixed states in patients with MDE according to different definitions. This post-hoc analysis evaluates the association between obesity and the presence of mixed features and bipolarity. Methods: 2811 MDE subjects were enrolled in this multicentre crosssectional study. In 2744 patients, the body mass index (BMI) has been evaluated.Psychiatric symptoms, socio-demographic and clinical variables were collected, comparing the characteristics of MDE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
1
22
0
2
Order By: Relevance
“…Briefly, investigators post hoc analyzed data from The Bipolar Disorders: Improving Diagnosis, Guidance and Education (BRIDGE)‐II‐Mix study wherein they sought to determine whether an association exists between mixed features and bipolarity among adults with a major depressive episode (MDE). The strength of the data was the sample size (ie, n = 2744) and the representativeness of the patients who were enrolled, assessed, and evaluated by highly experienced clinicians …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, investigators post hoc analyzed data from The Bipolar Disorders: Improving Diagnosis, Guidance and Education (BRIDGE)‐II‐Mix study wherein they sought to determine whether an association exists between mixed features and bipolarity among adults with a major depressive episode (MDE). The strength of the data was the sample size (ie, n = 2744) and the representativeness of the patients who were enrolled, assessed, and evaluated by highly experienced clinicians …”
mentioning
confidence: 99%
“…The strength of the data was the sample size (ie, n = 2744) and the representativeness of the patients who were enrolled, assessed, and evaluated by highly experienced clinicians. 2 The paper concluded that among adults meeting criteria for a MDE and comorbid obesity (ie, MDE-OB), 20% met criteria for bipolar disorder, 50% met criteria for the Angst bipolar specifier, and 13% for mixed features using either the DSM-5 criteria or the more encompassing (ie, including overlapping symptoms) Research-Based Diagnostic Criteria for Mixed State (RBDX-MSX). Moreover, MDE-OB individuals also were more likely to have other "bipolar probabilistic factors" (eg, higher number of prior episodes, atypical depressive features).…”
mentioning
confidence: 99%
“…The bipolarity‐obesity relationship is complex, a fact that is increasingly appreciated thanks to high‐quality studies such as the one recently published in Bipolar Disorders by Petri and colleagues . Previously, obesity in patients with psychiatric illness was viewed primarily as a consequence of treatment with weight‐gain‐promoting medications, and given what is known about many of the agents in this regard, this view is perhaps understandable.…”
mentioning
confidence: 99%
“…1 The bipolarity-obesity relationship is complex, a fact that is increasingly appreciated thanks to high-quality studies such as the one recently published in Bipolar Disorders by Petri and colleagues. 2 Previously, obesity in patients with psychiatric illness was viewed primarily as a consequence of treatment with weight-gain-promoting medications, and given what is known about many of the agents in this regard, this view is perhaps understandable. Placebo-controlled trials and clinical experience show convincingly that treatment with most mood stabilizers and second-generation antipsychotics (SGAs) and some antidepressants increases the likelihood of weight gain.…”
mentioning
confidence: 99%
“…As an objective measure of obesity, body mass index (BMI) in patients with psychiatric disorders, especially in schizophrenia and BP, have attracted researchers. In the article of “Obesity in patients with major depression is related to bipolarity and mixed features: evidence from the BRIDGE‐II‐Mix study,” Petri and colleagues used BMI ≥30 to divide 2811 patients with a MDE into two groups, MDE‐obesity group and MDE‐non‐obesity group, to study the association between obesity and bipolarity . The bipolarity included bipolar I and II disorders based on DSM‐IV, bipolar I and II specifier based on the DSM‐IV‐TR, depressive mixed state based on DSM‐5, and mixed depression based on the research‐based diagnostic criteria (RBDC).…”
mentioning
confidence: 99%